Usability improvements for touch-screen mobile flight booking application: a case study - Gündüz, Feyza; Pathan, Al-Sakib Khan (2012)
Smart phones have introduced great easiness in our daily life by mobile applications. Nowadays, it is possible to complete tasks on-the-go, without the need of computer. One of the facilities provided is the mechanism to buy flight tickets via mobile phones. However, in the development phase, often poor consideration of end-users’ usability requirements leads to underutilization of such facility, thus decreasing potential profit of companies. The purpose of this work is to investigate usability problems for mobile flight booking applications on touch-screen phones and suggest solutions. Main expectations of users are presented from HCI (Human Computer Interaction) perspective and discussed through a case study. Questionnaire and interview methods were used for collecting data. Paper prototype has also been utilized to verify users' expectations of mobile flight booking more accurately. Results reveal that the users are very much concerned with the easiness and the lucidness of functions. Usability is a highly considerable subject for users to prefer a mobile flight booking application over booking tickets via online/ or agencies.